Academic Self Efficacy dan Academic Stress pada Mahasiswa Baru yang Merantau - Zaneta Trixie Dacarent Thionata; Christiana Hari Soetjiningsih (Psikosains: Jurnal Penelitian dan Pemikiran Psikologi, 2023)
This study aims to find out the link between academic self efficacy and academic stress in new student who migrate. Participants in this survey consisted of 106 students from various universities in Indonesia obtained through convenience sampling techniques. The study uses two scales: academic self efficacy and academic stress. Data analysis using Spearman Rho’s correlation technique showed the existence of correlations of r= -0.417 with a significance value of 0,000 (p<0,05). The result showed that there is a students, which means that the greater the academic self efficacy of students, the lower will be experienced by new students. The result of this study can be a reference for new student who are studying in order to be able to improve their academic self efficacy so that they can minimize the occurrence of academic stress.